(untitled) (Journal of Engineering and Health Sciences, 2020)
The objective of this study is to study the biodiversity of Polygonum and to review its pharmacological properties and phytochemical compositions of via electronic literature search. The chemical composition, biological actions and the medicinal characteristics of P. minus(kesum) were mentioned in the articles. The chemical constituents include the polyphenols such as the flavonoids. The extracts were reported as anti-diabetic, anti-bacterial, anti-inflammatory and anti-cancer. This review is presented, in parallel with the laboratory experiments involving the separation of the Polygonum leaves extract using Thin Layer Chromatography. It is expected that the phytochemical data of the leaves would depend on the hydrophobicity of the aprotic solvent during the extraction procedure.